Response of leaf endophytic bacterial community to elevated CO2 at different growth stages of rice plant - Ren, Gaidi; Zhang, Huayong; Lin, Xiangui; Zhu, Jianguo; Jia, Zhongjun (Frontiers in Microbiology, 2015)
Plant endophytic bacteria play an important role in plant growth and health. In the context of climate change, the response of plant endophytic bacterial communities to elevated CO2 at different rice growing stages is poorly understood. Using 454 pyrosequencing, we investigated the response of leaf endophytic bacterial communities to elevated CO2 (eCO2) at the tillering, filling and maturity stages of the rice plant under different nitrogen fertilization conditions (low nitrogen fertilization (LN) and high nitrogen fertilization (HN)). The results revealed that the leaf endophytic bacterial community was dominated by Gammaproteobacteria-affiliated families, such as Enterobacteriaceae and Xanthomonadaceae, which represent 28.7-86.8% and 2.14-42.6% of the total sequence reads, respectively, at all tested growth stages. The difference in the bacterial community structure between the different growth stages was greater than the difference resulting from the CO2 and nitrogen fertilization treatments. The eCO2 effect on the bacterial communities differed greatly under different nitrogen application conditions and at different growth stages. Specifically, eCO2 revealed a significant effect on the community structure under both LN and HN levels at the tillering stage; however, the significant effect of eCO2 was only observed under HN, rather than under the LN condition at the filling stage; no significant effect of eCO2 on the community structure at both the LN and HN fertilization levels was found at the maturity stage. These results provide useful insights into the response of leaf endophytic bacterial communities to elevated CO2 across rice growth stages.